Associations of ofatumumab exposure and treatment outcomes in patients with untreated CLL receiving chemoimmunotherapy. Issue 2 (1st February 2017) - Jewell, Roxanne C.; Kipps, Thomas J.; Dürig, Jan; Griskevicius, Laimonas; Stilgenbauer, Stephan; Smolej, Lukáš; Mayer, Jiří; Hess, Georg; Hernandez-Ilizaliturri, Francisco J.; Padmanabhan-Iyer, Swaminathan; Fang, Lei; Goldstein, Nancy; et al.
Abstract: Relationships between patient characteristics, ofatumumab pharmacokinetics, and treatment outcomes were investigated in this phase 2 trial of ofatumumab plus fludarabine and cyclophosphamide (FC) in untreated chronic lymphocytic leukemia. Patients were randomized 1:1 to receive 500 or 1000 mg ofatumumab (Cycle 1; 300 mg) plus FC every 4 weeks for six cycles. Median Cmax and Ctrough values were similar at Cycle 1 regardless of the ultimate clinical outcome. At later doses, these values were higher for patients with complete response (CR) than for other patients. Higher Cmax and Ctrough values at Cycles 3 and 6 were significantly associated with an increased likelihood of CR, whereas ofatumumab pharmacokinetics were not associated with an objective response (OR) on the basis of univariate analyses. Multivariate analyses indicated that baseline patient/disease factors were predominantly associated with CR (17p status) or OR (bulky lymphadenopathy, gender, and serum thymidine kinase), rather than ofatumumab pharmacokinetics. Trial registration: www.clinicaltrials.gov (NCT00410163).